The Influence of Religiosity, Price Perceptions, Trends, and Lifestyle on Purchasing Decisions on Sharia Clothing - Ardilla Cintia (Journal of Financial and Business, 2024)
This research aims to determine the influence of religiosity, price perceptions, trends, and lifestyle on the decision to purchase Sharia clothing in the Muslim community in Tampan District, Pekanbaru City. The method used in this research is quantitative because the data in this research is in the form of numbers and analysis. The population in this research is the Muslim community of Tampan District, Pekanbaru City. A sample of 150 respondents used the accidental sampling technique. Meanwhile, the data analysis technique used is SEM-PLS. The test results showed that Religiosity had a significant influence on purchasing decisions, Price Perception had a significant influence on purchasing decisions, Trend had a significant influence on purchasing decisions, and Lifestyle did not influence purchasing decisions. The results of the F-Square test state that the most dominant independent variable influencing the decision to purchase Sharia clothing among the Muslim community in Tampan District, Pekanbaru City is the Religiosity variable. The author hopes that the results of this research can add insight to the body of knowledge and references that can be used as a source of information in a better order by the government in regulating and monitoring the development of the Sharia clothing industry.